Windows Server 2003 for Dummies - Tittel, Ed (John Wiley & Sons, 2011)
The perfect handbook for those who need to deploy, install, and configure installations, upgrade from previous versions, understand network addresses, manage day-to-day operations, configure storage, manage users and groups, implement security measures, configure mail services, and perform other vital administrative tasks. Covers the enhanced features and updates of the new version including the Microsoft .NET framework, Active Directory and its new drag and drop object management, Internet Information Server, and the Microsoft Management Console.